BUERGER’S DISEASE –TREATMENT WITH AYURVEDA: CASE STUDY (AYUSHDHARA, 2020)
Smoking is injurious to health. But those who are addicted to smoking never take this statement seriously. Nicotine present in tobacco causes vasospasm and inflammatory endarteritis. It is a prothombotic stage and subsequently causes vaso-occlusion. This usually affects lower limbs especially small and medium sized arteries. Disease progression is closely associated with heavy and continuous ingestion or inhalation of tobacco. Incidence of Burger’s disease is more common in men. It is very rare in females. Conservative treatments prescribed for this disease in initial phase were vasodilators, pentoxyphylline, low dose of aspirin, platelet aggregation inhibitor drugs. Surgical intervention involves chemical sympathectomy, lumbar sympathectomy and amputation of the gangrenous part. In Ayurveda Buerger’s disease is not mentioned. But with the symptoms and the pathology correlation to three Doshas it is possible to treat the disease. Here is a case study of male patient aged 32 years came with complaints of non healing ulcer which was created after amputation of all toes including great toes of right foot 6 months back. He was a chronic chain smoker and was diagnosed Buerger’s disease. He was given leech therapy once in 7 days along with oral Ayurvedic drugs and local application on wound.